2021
DOI: 10.1021/jacs.1c06115
|View full text |Cite
|
Sign up to set email alerts
|

Reacquainting the Electrochemical Conversion Mechanism of FeS2 Sodium-Ion Batteries by Operando Magnetometry

Abstract: In spite of the excellent electrochemical performance in lithiumion batteries (LIBs), transition-metal compounds usually show inferior capacity and cyclability in sodium-ion batteries (SIBs), implying different reaction schemes between these two types of systems. Herein, coupling operando magnetometry with electrochemical measurement, we peformed a comprehensive investigation on the intrinsic relationship between the ion-embedding mechanisms and the electrochemical properties of the typical FeS 2 /Na (Li) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 66 publications
2
60
0
Order By: Relevance
“…For instance, the conversion mechanisms of FeS 2 in Li/Na-ion batteries were comprehensively investigated by Li et al via operando magnetometry. [37] It is demonstrated that the FeS 2 does not reduce to metallic Fe in SIBs completely, resulting in inactive cores with a lower specific capacity. Furthermore, the diameter for reduced Fe particles in SIBs is clarified to be smaller than that in LIBs, which hints that a worse electrode pulverization happening in SIBs.…”
Section: Conversionmentioning
confidence: 98%
“…For instance, the conversion mechanisms of FeS 2 in Li/Na-ion batteries were comprehensively investigated by Li et al via operando magnetometry. [37] It is demonstrated that the FeS 2 does not reduce to metallic Fe in SIBs completely, resulting in inactive cores with a lower specific capacity. Furthermore, the diameter for reduced Fe particles in SIBs is clarified to be smaller than that in LIBs, which hints that a worse electrode pulverization happening in SIBs.…”
Section: Conversionmentioning
confidence: 98%
“…The simulation methods of LIBs are mainly divided into thermal simulation and electrochemical simulation. Thermal simulation is mainly used to simulate the model of LIBs temperature distribution, thermal behavior, and safety based on the experiments of battery materials and thermal properties 64–68 . Thermal simulation can be used to calculate the temperature variation and its distribution under different conditions (ambient temperature, battery short‐circuit, battery external damage, etc.).…”
Section: Principle Of Battery Heat Generationmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have been wildly used in small consumer electronics, electric vehicles, and medical apparatus as energy storage devices due to their advantages of high energy density, long cycle life, high working voltage, no memory effect, small self-discharge, and wide operating temperature range ( Sun et al, 2010 ; Wang et al, 2020c ; Gu et al, 2021 ; Li et al, 2021a ; Li et al, 2021b ; Li et al, 2021c ; Li et al, 2021d ; Zhao et al, 2021 ; Liang et al, 2022 ). However, to apply in large-scale energy storage projects and other high-power systems, the electrochemical properties of power density, rate capacity, cycle stability, and safety issue should be further improved ( Sun et al, 2011 ; Zhang et al, 2019b ; Wang et al, 2020b ; Zhang et al, 2020a ; Wang et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%